GENOMIC, EPIGENOMIC AND PROTEOMIC LANDSCAPING OF HEPATOCELLULAR CARCINOMA (International Association of Biologicals and Computational Digest, 2022)
Hepatocellular carcinoma (HCC) is one of the most common and fatal malignancy in humans and proves to be the third most common cause of cancer-related death. Thus, HCC contributes to major international health problem because its incidence is exponentially increasing in many countries. One of the main reasons for the lethality of HCC is the lack of diagnostic markers for early detection of the disease. At late stages, HCC shows a high clinical heterogeneity with poor prognosis i.e. high tumor recurrence is observed in 60-70% of cases within 5 years after surgery. One of the major reasons is that most patients with HCC were diagnosed at advanced stages. It is crucial to find out new therapeutic targets and novel diagnostic biomarkers for the early diagnosis and timely treatment of HCC and to develop preventive strategies and therapeutic interventions based on an improved understanding of molecular hepato carcinogenesis. Therefore, it is still urgent to further explore the exact molecular mechanisms of the development, progression, invasion, and metastasis of HCC. It has been shown that both genetic and epigenetic alterations are crucial for the initiation of HCC, thus making epigenetics a promising and attractive field for identifying the subset of patients at a high risk of recurrence and with dismal survival outcomes.However, the underlying molecular mechanisms remain unknown. Thus, it is urgent and important to dig the hub molecules and to uncover the key molecular mechanisms. Due to the advances made in research based on next generation sequencers, it is now possible to detect and analyse epigenetic abnormalities associated with cancer. In this review article we are trying to explore previously reported to play key role in HCC development and progression such as, DNA methylation, various histone modifications, chromatin remodelling, and non-coding RNA associated gene silencing are considered to be transcriptional regulatory mechanisms associated with gene expression changes.
Keywords: Hepatocellular Carcinoma,DEGs ,miRNAs,lncRNA